Wet-mode magnetic classification: Proofing the concept - barbosa, d (2017)
There is a clear need to develop processing techniques that may allow to selectively separate and purify several substances at the same step and in the same device, especially in what concerns biomedical applications (ranging from diagnostics until treatment of diseases), as modern technologies are still very limited regarding this goal. Magnetic separation is a classical technique that may be applied nowadays to separate and purify potentially any substance, when allied to magnetic tagging and carrier technologies. However it also has the same limitation of selectively separating only a single particle/substance in one step. To overcome this limitation, we have been developing an area which is denominated as magnetic classification that is potentially capable of selectively separating substances (applying or not magnetic tags) from each other using only one single step and one machine. The research on this area so far has been limited. In this work we present a proof of concept on magnetic classification in wet mode, in such a way that we were able to show its feasibility for biological and biomedical media. Based on the preliminary results we are now ready to develop, design and control a larger scale device for future applications.